Bioequivalence study of fixed-dose combination Losartan + amlodipine + rosuvastatin Sanofi in comparison with coadministered fixed- dose combination Lozap® AM and monocomponent drug Crestor® in healthy subjects - A. L. Khokhlov; D. Yu. Grebenkin; E. K. Faeva; V. I. Kazey; A. A. Khokhlov; A. E. Miroshnikov; O. V. Lebedeva (LLC "Publisher OKI", 2022)
Introduction. The advantages of fixed-dose combination losartan + amlodipine + rosuvastatin compared to mono-drugs and two-component combinations are to increase the therapeutic efficacy, to reduce the cost of the product and to make the drug easier to take which helps to improve patient adherence to therapy. A bioequivalence study of the three-component fixed-dose combinations Losartan + amlodipine + rosuvastatin Sanofi with coadministered Lozap® AM (Losartan+Amlodipine) and Crestor® (Rosuvastatin) was conducted.   Aim. The purpose of the bioequivalence trial was a comparative study of the pharmacokinetics and evidence of the bioequivalence of two strengths of fixed-dose combination: 1) Losartan + amlodipine + rosuvastatin Sanofi (tablets, 50 mg + 5 mg + 10 mg) in comparison with coadministrated drugs Lozap® AM (losartan + amlodipine, tablets, 50 mg + 5 mg,) and Crestor® (rosuvastatin, tablets, 10 mg) in fasting healthy volunteers after a single administration; 2) Losartan + amlodipine + rosuvastatin Sanofi (tablets, 100 mg + 5 mg + 20 mg) in comparison with coadministrated drugs Lozap® AM (losartan + amlodipine, tablets, 100 mg + 5 mg) and Crestor® (rosuvastatin, tablets, 20 mg) in fasting healthy volunteers 18-45 years old after a single dose.   Materials and methods. To prove bioequivalence, an open label, comparative, randomized, crossover four-period clinical trial was conducted for each strengths of fixed-dose combination. The concentrations of losartan, amlodipine and rosuvastatin in blood plasma samples obtained from volunteers were determined by a validated HPLC-MS/MS method. A pharmacokinetic and statistical analysis was performed and confidence intervals (CI) for the pharmacokinetic parameters Сmax, AUC0-72 (for amlodipine) and AUC0-t (for losartan and rosuvastatin) were calculated.      Results and discussion. Based on the results of statistical and pharmacokinetic analysis, it was shown that the studied formulations are bioequivalent in terms of pharmacokinetic parameters of losartan, amlodipine and rosuvastatin. 90 % CI were in the acceptable range for Сmax (of amlodipine), AUC0-72 (of amlodipine) and AUC0-t (of losartan and rosuvastatin). 90 % CI for Сmax of losartan and rosuvastatin were in the acceptable extended calculated range according to the protocol.   Conclusion. Thus, according to the criteria used in the studies, the three-component fixed-dose combinations Losartan + amlodipine + rosuvastatin Sanofi are proved to be bioequivalent in comparison with coadministered Lozap® AM and Crestor®.